Source of Previous Treatment for Re-Treatment TB Cases Registered under the National TB Control Programme, India, 2010 - Sachdeva, Kuldeep Singh (Public Library of Science, 2011)
BACKGROUND: In 2009, nearly half (289,756) of global re-treatment TB notifications are from India; no nationally-representative data on the source of previous treatment was available to inform strategies for improvement of initial TB treatment outcome. OBJECTIVES: To assess the source of previous treatment for re-treatment TB patients registered under India's Revised National TB control Programme (RNTCP). METHODOLOGY: A nationally-representative cross sectional study was conducted in a sample of 36 randomly-selected districts. All consecutively registered retreatment TB patients during a defined 15-day period in these 36 districts were contacted and the information on the source of previous treatment sought. RESULTS: Data was collected from all 1712 retreatment TB patients registered in the identified districts during the study period. The data includes information on 595 ‘relapse’ cases, 105 ‘failure’ cases, 437 ‘treatment after default (TAD)’ cases and 575 ‘re-treatment others’ cases. The source of most recent previous anti-tuberculosis therapy for 754 [44% (95% CI, 38.2%–49.9%)] of the re-treatment TB patients was from providers outside the TB control programme. A higher proportion of patients registered as TAD (64%) and ‘retreatment others’ (59%) were likely to be treated outside the National Programme, when compared to the proportion among ‘relapse’ (22%) or ‘failure’ (6%). Extrapolated to national registration, of the 292,972 re-treatment registrations in 2010, 128,907 patients would have been most recently treated outside the national programme. CONCLUSIONS: Nearly half of the re-treatment cases registered with the national programme were most recently treated outside the programme setting. Enhanced efforts towards extending treatment support and supervision to patients treated by private sector treatment providers are urgently required to improve the quality of treatment and reduce the numbers of patients with recurrent disease. In addition, reasons for the large number of recurrent TB cases from those already treated by the national programme require urgent detailed investigation.